Observation of exclusive (B)over-bar -> (DK*-)-K-(*) decays - Mahapatra, R; Nelson, H; Briere, R; Chen, G; Ferguson, T; Tatishvili, G; Vogel, H; Adam, N; Alexander, J; Bebek, C; Berkelman, K; Blanc, F; et al. (2002)
The exclusive decays B̄ → D(*)K*-, using 9.66 × 106 BB̄ pairs collected at the γ(4S) with the CLEO detector was reported. Some branching fractions were measured such as β(B- → D0K*-) = (6.1 ± 1.6 ± 1.7) × 10-4. It was found that the B̄ → D*K*- branching ratios were averages of those corresponding to the 00 and 11 helicity states.